2007
DOI: 10.1007/s00701-007-1234-x
|View full text |Cite
|
Sign up to set email alerts
|

Rathke’s cleft cysts: differentiation from other cystic lesions in the pituitary fossa by use of single-shot fast spin-echo diffusion-weighted MR imaging

Abstract: DWI-SSFSE with ADC values provides objective information in the differential diagnosis of Rathke's cleft cysts from other sellar cystic lesions. In addition, DWI-SSFSE with ADC values is useful for differentiating Rathke's cleft cysts from craniopharyngiomas and haemorrhagic pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…A pseudo-fluid-fluid level may be observed in craniopharyngiomas, corresponding to tenacious secretions or the position of the interface between the fluid and solid components of the tumor (26). Furthermore, diffusion-weighted MRI and relative apparent diffusion coefficient, as well as clinical presentation and endocrine appearance, have been suggested to be beneficial in differentiating among pituitary adenomas, RCCs, craniopharyngiomas and other cystic sellar lesions (28).…”
Section: Discussionmentioning
confidence: 99%
“…A pseudo-fluid-fluid level may be observed in craniopharyngiomas, corresponding to tenacious secretions or the position of the interface between the fluid and solid components of the tumor (26). Furthermore, diffusion-weighted MRI and relative apparent diffusion coefficient, as well as clinical presentation and endocrine appearance, have been suggested to be beneficial in differentiating among pituitary adenomas, RCCs, craniopharyngiomas and other cystic sellar lesions (28).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] However, it is difficult to evaluate skull base structures by the most common imaging technique used with echo-planar (EP)-DWI. Previous studies have revealed the efficacy of DWI for skull base tumors such as pituitary adenoma; however, they are mostly limited to macroadenomas large enough to calculate the ADC by using EP sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, previous studies by using EP-DWI were mainly limited to pituitary macroadenoma, apoplexy, abscess, or other parasellar lesions. [3][4][5][6][7] Other researchers applied non-EP-DWI such as single-shot fast spinecho, 8 line scan, 9 and periodically rotated overlapping parallel lines with enhanced reconstruction 10 DWI for sellar and parasellar lesions to overcome image degradation. In the present study, we used DSDE-TFE, which enabled us to obtain a 3D dataset and high spatial resolution (1.5 ϫ 1.5 ϫ 1.5 mm 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a radiological diagnosis of CP was supported by features such as superior tumor lobulation, larger tumor volume, compression of the third ventricle, and a reticular enhancement pattern of the solid tumor portion. Kunii et al 57 used single-shot fast spin echo diffusion weighted MR imaging to differentiate cystic sellar and suprasellar lesions. They reported that RCCs could be identified using this imaging modality because of the lesion's increased regional apparent diffusion coefficient values, in contrast with those of CPs and hemorrhagic pituitary adenomas.…”
Section: Imaging Featuresmentioning
confidence: 99%